Герои неба. Летчики военной авиации - Чумаков Ян Леонидович (1941-1945. Великая и неизвестная война, 2020)
Экземпляры: Чз (20211115) / Инвентарный номер: 48907 / Цена: / Авт.знак: Ч-90 / ГРНТИ: 03.23.55 / ББК: 63.3(2)622